2018
DOI: 10.1029/2018jf004622
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Sediment Transport Dynamics on Alluvial Fans From Spatial and Temporal Changes in Grain Size, Death Valley, California

Abstract: How information about sediment transport processes is transmitted to the sedimentary record remains a complex problem for the interpretation of fluvial stratigraphy. Alluvial fan deposits represent the condensed archive of sediment transport, which is at least partly controlled by tectonics and climate. For three coupled catchment‐fan systems in northern Death Valley, California, we measure grain size across 12 well‐preserved Holocene and late‐Pleistocene surfaces, mapped in detail from field observations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 132 publications
2
22
0
Order By: Relevance
“…Finally, we did not explicitly include a grain-size specific hiding (e.g., Eq. A8 in Pfeiffer and Finnegan, 2018) or a protrusion function (e.g., Carling, 1983;Sear, 1996;van der Berg and Schlunegger, 2012) in our analysis, but we suggest that the selected range between 0.03 and 0.06 considers most of the complexities and scatters of φ values that are related to the hiding of small clasts and the protrusion of large constituents (Buffington et al, 1992;Buffington and Montgomery, 1997;Kirchner et al, 1990;Johnston et al, 1998). In summary, we infer that the selection of uniformly distributed φ values between 0.03 and 0.06 does account for the large variability of φ values that are commonly encountered in experiments and field surveys where energy gradients range between 0.001 and 0.02, which is the case here.…”
Section: Monte Carlo Simulationsmentioning
confidence: 80%
See 1 more Smart Citation
“…Finally, we did not explicitly include a grain-size specific hiding (e.g., Eq. A8 in Pfeiffer and Finnegan, 2018) or a protrusion function (e.g., Carling, 1983;Sear, 1996;van der Berg and Schlunegger, 2012) in our analysis, but we suggest that the selected range between 0.03 and 0.06 considers most of the complexities and scatters of φ values that are related to the hiding of small clasts and the protrusion of large constituents (Buffington et al, 1992;Buffington and Montgomery, 1997;Kirchner et al, 1990;Johnston et al, 1998). In summary, we infer that the selection of uniformly distributed φ values between 0.03 and 0.06 does account for the large variability of φ values that are commonly encountered in experiments and field surveys where energy gradients range between 0.001 and 0.02, which is the case here.…”
Section: Monte Carlo Simulationsmentioning
confidence: 80%
“…Using the results of flume and numerical experiments, Jerolmack and Paola (2010) suggested that these source signals are likely to be shredded during sediment transport as a consequence of what they considered as ubiquitous thresholds in sediment transport systems. However, based on a detailed analysis of downstream fining trends in alluvial fan deposits, Whittaker et al (2011), D'Arcy et al (2017 and Brooke et al (2018) proposed that primary source signals of grain size compositions are likely to propagate farther downstream in a self-similar way. Accordingly, the original grain-size sorting of the supplied material could be maintained although a general fining of the sediments along the sedimentary routing system would be observed.…”
Section: Controls On the Sorting Of The Bed Materialsmentioning
confidence: 99%
“…coinciding with a switch to incision) and so can, in principle, be defined with greater precision. For surfaces with an extended period of formation, the timing of abandonment is more likely to coincide with events of interest such as reorganization of a drainage network (Bufe et al, 2017); changes in climate, sediment supply, or base level (Steffen et al, 2009;Tofelde et al, 2017;Mouslopoulou et al, 2017;Brooke et al, 2018); or tectonic deformation such as faulting, uplift, or subsidence (e.g. Frankel et al, 2007Frankel et al, , 2011Ganev et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…been established (e.g., Brooke et al, 2018;D'Arcy et al, 2017;Litty, Schlunegger, & Viveen, 2017). Multiple studies demonstrated that grain size exported from catchments with similar climate and tectonic characteristics can vary due to differences in catchment lithology (e.g., Allen et al, 2015;Rădoane, Rădoane, Dumitriu, & Miclăuş, 2008;Roda-Boluda et al, 2018).…”
Section: Highlightsmentioning
confidence: 99%
“…Basin stratigraphic architecture is fundamentally determined by the magnitude of sediment supply (Allen & Densmore, 2000;Armitage, Duller, Whittaker, & Allen, 2011;Cowie et al, 2006;Densmore, Allen, & Simpson, 2007;Forzoni, Storms, Whittaker, & Jager, 2014;Leeder, Harris, & Kirkby, 1998;Pechlivanidou et al, 2018), and the grain-size distribution within that supply (Allen et al, 2015;Armitage et al, 2011;Brooke, Whittaker, Armitage, D'Arcy, & Watkins, 2018;Hampson, Duller, Petter, Robinson, & Allen, 2014). In particular, well-constrained measures of grain-size in fluvial systems can be used to reconstruct palaeoslopes (Cassel & Graham, 2011;Duller et al, 2012;Garefalakis & Schlunegger, 2018;Paola & Mohrig, 1996), estimate tectonic subsidence rates through downstream fining (Michael, Whittaker, Carter, & Allen, 2014;Parsons, Michael, Whittaker, Duller, & Allen, 2012) and infer drier or wetter periods through time (Brooke et al, 2018;D'Arcy, Roda-Boluda, & Whittaker, 2017). Grain-size also plays a fundamental role in determining the spatiotemporal scales over which internal dynamics of sedimentary systems operate (Ganti, Lamb, & McElroy, 2014) and dictates sediment facies partitioning within subsiding depocentres (Allen et al, 2013;Armitage et al, 2011Armitage et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%